Step-by-step explanation:
(-11/6) + m = -2/9
m = -2/9 + 11/6
the last common multiple of 9 and 6 is 18.
so, we are bringing both fractions to .../18.
m = -2×2/18 + 11×3/18 = -4/18 + 33/18 = 29/18
Simplifying h(x) gives
h(x) = (x² - 3x - 4) / (x + 2)
h(x) = ((x² + 4x + 4) - 4x - 4 - 3x - 4) / (x + 2)
h(x) = ((x + 2)² - 7x - 8) / (x + 2)
h(x) = ((x + 2)² - 7 (x + 2) - 14 - 8) / (x + 2)
h(x) = ((x + 2)² - 7 (x + 2) - 22) / (x + 2)
h(x) = (x + 2) - 7 - 22/(x + 2)
h(x) = x - 5 - 22/(x + 2)
An oblique asymptote of h(x) is a linear function p(x) = ax + b such that
In the simplified form of h(x), taking the limit as x gets arbitrarily large, we obviously have -22/(x + 2) converging to 0, while x - 5 approaches either +∞ or -∞. If we let p(x) = x - 5, however, we do have h(x) - p(x) approaching 0. So the oblique asymptote is the line y = x - 5.
14 = 9 - x
First, subtract 9 from both sides.
14 - 9 = (9 - 9) - x
5 = -x
Now divide both sides by -1.
5/-1 = -1/-1x
-5 = x
The answer is x = -5.
from least to greatest: 0.85, 8/9 (0.88 as a decimal), 0.93
Answer:
I think the answer is y = 3x + 12.
Step-by-step explanation:
y = 3 (x - 1) (x - 4)
y = 3x -3 (x - 4)
y = 3x + 12